Paroxysmal Permeability Disorders: Development of a Microfluidic Device to Assess Endothelial Barrier Function - Wu, Maddalena Alessandra; Tsvirkun, Daria; Bureau, Lionel; Boccon-Gibod, Isabelle; Inglebert, Mehdi; Duperray, Alain; Bouillet, Laurence; Misbah, Chaouqi; Cicardi, Marco (Frontiers in Medicine, 2019)
Background: Paroxysmal Permeability Disorders (PPDs) are pathological conditions caused by periodic short lasting increase of endothelial permeability, in the absence of inflammatory, degenerative, ischemic vascular injury. PPDs include primary angioedema, idiopathic systemic capillary leak syndrome and some rare forms of localized retroperitoneal-mediastinal edema. Aim: to validate a microfluidic device to study endothelial permeability in flow conditions. Materials and Methods: we designed a microchannel network (the smallest channel is 30μm square section). Human Umbilical Vein Endothelial Cells (HUVECs) were cultured under constant shear stress in the networks. Endothelial permeability assessment was based on interaction of biotinylated fibronectin used as a matrix for HUVECs and FITC-conjugated avidin. The increase in endothelial permeability was identified as changes in fluorescence intensity detected by confocal fluorescent microscopy. Results: The microchannels were constantly perfused with a steady flow of culture medium, ensuring a physiologically relevant level of shear stress at the wall of ~0.2 Pa. Our preliminary results demonstrated that circulation of culture medium or plasma from healthy volunteers was associated with low fluorescence of fibronectin matrix. When bradykinin diluted in culture medium was perfused, an increase in average fluorescence was detected. Conclusion: Our microvasculature model is suitable to study endothelial functions in physiological flow conditions and in the presence of factors like bradykinin known as mediator of several PPDs. Therefore, it can be a promising tool to better understand the mechanisms underlying disorders of endothelial permeability.